Qur’an Recitation Therapy as Anxiety Treatment - Carla Raymondalexas Marchira (HM Publisher, 2020)
Anxiety is an uncomfortable, pleasant, indistinct and pleasant feeling with autonomic symptoms. Many internal and external factors cause anxiety in a person. The human body tries to maintain homeostasis at all times. Anything that disrupts homeostasis is defined as a stressor by the body. To compensate for stressors and to restore homeostatic equilibrium, physiological adaptations occur in response to stress. This adaptation involves a hormonal cascade along the HPA axis, namely the release of corticotropin-releasing factor (CRF) which stimulates the release of adrenocorticotropic hormone (ACTH) and causes the release of stress hormones (glucocorticoids and epinephrine) from the adrenal cortex. Glucocorticoids will provide negative feedback (negative feedback) to the hypothalamus, thereby reducing the release of CRF. Non-pharmacological intervention anxiety that has lower side effects is safer and can be used for a more extended period compared to anti-anxiety drugs. The recitation of the Al-Qur'an generates alpha waves, which are waves that appear when someone is relaxing. Increased alpha waves can reduce symptoms of anxiety.